Relationship between emotional and spiritual intelligences and mental health problems among Iranian high school students - Shabani, Jafar (2011)
The purpose of this study was to investigate the relationship between emotional and spiritual intelligences scale and sub-scales with mental health problems scale and sub- scales among Iranian high school students. The participants in the study included 10th, 11th, and 12th grade students from eight public high schools in Gorgan City, north of Iran. They were 247 high school students, specifically comprised 124 boys and 123 girls, age ranged between 15 to 17 years old. The sample responded to three valid and reliable instruments, which were 1) Emotional Quotient Inventory, Youth Version (EQ-i YV); 2) Integrated Spiritual Intelligence Scale (ISIS); and 3) General Health Questionnaire (GHQ 28). This research utilized the ex post facto research design. The researcher was interested to investigate the relationship of emotional and spiritual intelligences scale and sub-scales with mental health problems scale and sub-scales, as well as whether or not mental health problems scale and sub-scales could be predicted by emotional and spiritual intelligences scale and sub-scales. In addition, it sought to examine the significant differences of mental health problems scale and sub-scales concerning the participants‟ gender and age. Finally, this study examined the moderation effects of gender and age on the relationships of emotional and spiritual intelligences with mental health problems. Data analysis included frequencies, percentages, mean scores, as well as multiple and moderated regressions. SPSS for Windows at alpha level .05 computed the statistical data. The findings of this study revealed significant but negative relationship between total emotional intelligence, interpersonal, adaptability, stress management, and general mood with mental health problems scale and sub-scales. Thus, these variables were found significantly related to mental health problems scale and sub-scales. Nevertheless, there was no significant relationship between one of the emotional intelligence sub-scales (intrapersonal) and mental health problems scale and sub-scales. The hypotheses also denoted the negatively significant relationship between total spiritual intelligence, consciousness, grace, meaning, transcendence, and truth, with total mental health problems, social dysfunction, and depression, as well as, negatively significant relationship between total spiritual intelligence, grace,meaning, transcendence, and truth, with somatic symptoms and anxiety. Regression linear analysis showed that some predicting variables (total emotional and spiritual intelligences, general mood, grace, truth, and stress management) were found to be of significance in explaining mental health problems scale and sub-scales. In sum, the results of this study support the theories that emotional and spiritual intelligences are predictors for mental health problems scale and sub-scales. Results of t-test showed that there was no significant mean difference between male and female students and their mental health problems scale and sub-scales. The results of one-way ANOVA revealed that there was no significant mean difference between students‟ age groups (15th, 16th, and 17th) and their mental health scale and sub-scales. Finally, the results indicated that gender and age were not moderators for the relationship between emotional and spiritual intelligences and students‟ mental health problems. Hence, gender and age as moderating variables did not influence the relationship between emotional and spiritual intelligences with mental health problems.